The Factors Affecting Broiler Chicken Demand in Kendari City During the Covid-19 Pandemic - Melani Melani; Muhammad Aswar Limi; Agustono Slamet (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
This study intends to raise the demand for broiler chickens in Kendari City during the Covid-19 epidemic. Factors influencing the demand for broiler chickens in Kendari City during the Covid-19 epidemic. This time, the decision of the place was made consciously. Held in Baruga Market, Anduonohu Market, Lapulu Market, Korem Side Market, and Bonggoeya Traditional Market from August to September 2021. The Accidental sampling method based on chance was used to choose the sampling strategy for this investigation. If it is determined that the individual the researcher encounters by chance is appropriate as a data source, then they may be employed as a sample. 100 people who regularly eat broiler chicken made up the study's sample. Analysis using multiple linear regressions. The variables observed in this research are the cost of broiler chicken, consumer income, age, the expenditure on fish, the price of chicken eggs, and the family size. According to the study, broiler chicken is naturally needed 5,95 times a month in Kendari City. The main elements influencing this requirement are the stock price, income, and tours (t 0,05). The demand for broiler chicken during the pandemic cord 19 in Kendari City is highly influenced by the price of fish, chicken eggs, and the household size (t > 0,05).